Orthodox tradition and human sexuality - Arentzen, Thomas 1976-; Purpura, Ashley M.; Papanikolaou, Aristotle ca. 21. Jh (Fordham University Press, 2022)
"Sex is a difficult issue for contemporary Christians, but the past decade has witnessed a newfound openness regarding the topic among Eastern Orthodox Christians. Both the theological trajectory and the historical circumstances of the Orthodox Church differ radically from those of other Christian denominations that have already developed robust and creative reflections on sexuality and sexual diversity. Within its unique history, theology, and tradition, Orthodox Christianity holds rich resources for engaging challenging questions of sexuality in new and responsive ways. What is at stake in questions of sexuality in the Orthodox tradition? What sources and theological convictions can uniquely shape Orthodox understandings of sexuality? This volume aims to create an agora for discussing sex, and not least the sexualities that are often thought of as untraditional in Orthodox contexts. Through fifteen distinct chapters, written by leading scholars and theologians, this book offers a developed treatment of sexuality in the Orthodox Christian world by approaching the subject from scriptural, patristic, theological, historical, and sociological perspectives. Chapters devoted to practical and pastoral insights, as well as reflections on specific cultural contexts, engage the human realities of sexual diversity and Christian life. From re-thinking scripture to developing theologies of sex, from eschatological views of eros to re-evaluations of the Orthodox responses to science, this book offers new thinking on pressing, present-day issues and initiates conversations about homosexuality and sexual diversity within Orthodox Christianity"--
Keywords: Sex / Religious aspects / Orthodox Eastern Church; Orthodox Eastern Church / Doctrines; Sexualité / Aspect religieux / Église orthodoxe; Orthodox Eastern Church; Theology, Doctrinal; Aufsatzsammlung